DEVELOPMENT OF LEARNING TOOLS FOR ALGEBRAIC FORMS BASED ON PBL MODELS TO FACILITATE KPMM FOR CLASS VII STUDENTS OF SMP/MTs - Nur Almira; Susda Heleni (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2022)
This research produces a product in the form of a mathematics learning device using a Problem-Based Learning model on Algebraic Form material to facilitate students' Mathematical Problem-Solving Ability. Learning tools developed in the form of syllabus, lesson plan (RPP), and student worksheets (LKPD). The development model used is a 4-D model, where the stages are defined, designed, developed, and disseminated. The validity of the instrument is in the form of a validation sheet to assess the validity of the learning tools, namely the syllabus, lesson plans, and LKPD. Practical instruments in the form of student response questionnaires to assess the usefulness and ease of use of LKPD. Three validators will validate and revise it according to the validator's suggestions. Then a limited group trial was conducted with eight students. Based on the results of the validation data analysis, it was concluded that this mathematics learning tool was very valid, with an average score of 3.79 for the syllabus, 3.56 for lesson plans, and 3.52 for LKPD. Based on the results of practicality data analysis, the student response questionnaire showed a very practical category with an average rating of 3.59.